Big little spells - Beck, Hazel (Beck, Hazel. Witchlore series, 2023)
Returning to her coven ten years after being stripped of her magic and banished, Rebekah faces a death sentence as a danger to witchkind in the second novel of the series following Small Town, Big Magic.